Creating and sustaining competitiveness: an analysis of the Japanese robotics industry. (4th August 2014) - Bowonder, B.; Miyake, T.
Initially the major Japanese firms acquired their robotics technology from US firms. The Japanese firms have dynamically developed the competitiveness from then on through globalization, alliances and innovation. Their approach was to assess the generic skills needed for sustaining the competitiveness, and to develop these skills at the level of the firm. Functional integration helped the firms to learn and accumulate new skills faster than their competitors.